Community development through community capacity building: a social science perspective - Md. Sail, Rahim; Abu Samah, Asnarulkhadi (Marsland Press, 2010)
Community development is a continuous process aimed at improving the quality of life of the community. It is about continual improvement by the people themselves to bring about change in their lives. In relation to health, much attention has been given by the government to improve the health status of the people, especially the rural sector through various programmes established by the Ministry of Health (MOH) since independence. Based on the so-called “state-sponsored programme”, the health status of the majority of Malaysians has improved over the years. The objectives of the health care providers are not only providing health services but also improving the quality of services for the people. In such an orientation, the community is perceived mainly as clients by the health provider. The community’s participation in health related programmes or activities are basically measured by the number of clients’ visits to the clinics, decrease in the defaulter rate or prevalence of diseases and other quantifiable indicators. The qualitative aspects of community members’ involvement in health related activities as a process of empowerment within the coverage of the care providers have been given less priority. Based on this premise, this paper discusses on community capacity building as an important component and process of community development.